Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.15376/biores.14.4.8484-8498
|View full text |Cite
|
Sign up to set email alerts
|

Polylactic acid-based wood-plastic 3D printing composite and its properties

Abstract: Wood-plastic composites for 3D printing from plant fiber (bleached pulp powder, mechanical pulp powder, newspaper pulp powder, eucalyptus powder, pine powder, and lignin) and polylactic acid (PLA), with silane coupling agent (KH550) as plasticizer, were prepared via melt extrusion. The physical properties, such as surface morphology, apparent density, tensile strength, melt flow rate, compatibility, and thermal stability were measured. Moreover, the effects of the content of various types of plant fiber powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Liu et al observed enhanced tensile strength from FDM printed materials with 15% of lignin addition to PLA compared to that of pure PLA and other PLA/biomass composites. 90 Mimini et al investigated the chemical structures, thermal properties, printability with FDM, and physical properties of PLA-based composites blended respectively with pine kra lignin, beech organosolv lignin, and beech LS. 91 All the three materials had slightly lower thermal stability and impact strength when those lignin contents increased (up to 15 wt%).…”
Section: Ligninmentioning
confidence: 99%
“…Liu et al observed enhanced tensile strength from FDM printed materials with 15% of lignin addition to PLA compared to that of pure PLA and other PLA/biomass composites. 90 Mimini et al investigated the chemical structures, thermal properties, printability with FDM, and physical properties of PLA-based composites blended respectively with pine kra lignin, beech organosolv lignin, and beech LS. 91 All the three materials had slightly lower thermal stability and impact strength when those lignin contents increased (up to 15 wt%).…”
Section: Ligninmentioning
confidence: 99%
“…In addition, it has been found that the properties of composites (such as interfacial adhesion and thermal properties) were improved as a result of the addition of modified wood/plant fibers to the polymer matrix (Csizmadia et al 2013;Wei et al 2013;Spiridon et al 2016;Zhang et al 2017;Narlıoğlu 2018;Yang et al 2020). The compatibility of PLA polymer was improved after plant fibers were treated with silane coupling agent (KH-550) (Liu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increasing demand and rising production costs of synthetic polymers, researchers have focused on the production of low-cost and sustainable raw materials for the 3D printer filaments and the improvement of their properties. Most of these studies have focused on the biodegradable PLA polymer and wood fibers (Tao et al 2017;Liu et al 2019b;Bhagia et al 2020;Kain et al 2020). Polylactic acid polymer has been preferred in much academic research in 3D printer applications due to its easy production, affordable production costs, and biodegradable properties (Yang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is continual research to improve the printing performance of PLA-derived wood plastic composites in 3D printers. Studies have shown that the variety and amount of plant fibers in the filaments significantly affect the performance of the printed composites (Stoof et al 2017;Liu et al 2019b;Mazzanti et al 2019). It was also reported that woodplastic composite filaments prepared by adding certain proportions of plant fibers into the PLA matrix slightly offset the disadvantages of the PLA polymer, which reduces the final production costs and provides a natural appearance to the 3D printed products (Liu et al 2019b).…”
Section: Introductionmentioning
confidence: 99%